Understanding the behaviour of Malaysian green investors - Azrai Azaimi Ambrose, Azniza Hartini; Peredaryenko, Margarita Sergeevna; Mustaffa Kamil, Nazrol Kamil; Mohd Nasarudin, Ahmad Fawwaz (Inderscience Publishers, 2023)
The Malaysian Government is committed to enact green economy in the region. Yet studies in green investor behaviour are scanty at best. This proves unpropitious for a comprehensive understanding of green investor behaviour may be the key to further the green sustainability cause of the region. This research fills this gap by interviewing Malaysian green investors and examining the interview transcripts using thematic analysis. Questions pertaining to attitude, belief, value, challenge, and process in reference to green investment were inquired. The findings demonstrate certain behaviours that can be useful to academicians in theory development and policy makers in advancing the Malaysian green sustainability agenda.